2019
DOI: 10.1029/2019jc015071
|View full text |Cite
|
Sign up to set email alerts
|

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas

Abstract: In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 105 publications
2
47
0
Order By: Relevance
“…Journal of Geophysical Research: Oceans East Antarctica (Moreau et al, 2019). Correspondingly, the relative importance of the different dFe sources obtained from this simulation shows regional variability.…”
Section: 1029/2019jc015736mentioning
confidence: 64%
“…Journal of Geophysical Research: Oceans East Antarctica (Moreau et al, 2019). Correspondingly, the relative importance of the different dFe sources obtained from this simulation shows regional variability.…”
Section: 1029/2019jc015736mentioning
confidence: 64%
“…These corresponding impacts to the CO 2 system have been primarily attributed to an enhancement in biological production as a result of large increases in sea ice meltwater, potentially delivering a source of dissolved iron to the mixed layers (Shadwick et al, ). A recent analysis by Moreau et al () concluded that a larger volume of sea ice meltwater in the Mertz Polynya and neighboring Ninnis Polynya best explained their enhanced biological productivities relative to the Dalton Polynya. The calving of the MGT in the Mertz Polynya set up an interesting natural experiment to assess how changes to the Antarctic icescape impact polynya productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the Terra Nova Bay (TNB) polynya in the western Ross Sea (163–167°E), late summer NCP is an order of magnitude larger than the Dalton polynya at roughly 425 mmol C m −2 day −1 (Table ; DeJong et al, ). Biological production in TNB is typically dominated by diatoms in summer when stratification is stronger and mixed layers are shallower (Arrigo et al, ; Tortell et al, ), in contrast to the Phaeocystis antarctica communities in the Dalton Polynya (Moreau et al, ). Polynya formation in TNB is primarily driven by intense offshore katabatic winds (Bromwich & Kurtz, ) that prevent a consolidated sea ice pack from forming in the lee of the Drygalski Ice Tongue, with wind speeds often ranging between 10 and 30 m/s (Bromwich, ).…”
Section: Discussionmentioning
confidence: 99%
“…Polynyas are areas where particle fluxes are expected to be significant, and they also harbor high densities of upper trophic level organisms such as birds and marine mammals (Karnovsky et al, 2007). Further information regarding the sampling area can be found in Moreau et al (2019). Samples were collected at two mesopelagic depths (100 and 300 m), using either a 12L-Niskin bottle (BTL-samples) or an in situ pump (ISP-samples) deployed at each depth.…”
Section: Study Areamentioning
confidence: 99%